2021
DOI: 10.3390/ijms22095037
|View full text |Cite
|
Sign up to set email alerts
|

Wound Repair and Extremely Low Frequency-Electromagnetic Field: Insight from In Vitro Study and Potential Clinical Application

Abstract: Wound healing is a complex, staged process. It involves extensive communication between the different cellular constituents of various compartments of the skin and its extracellular matrix (ECM). Different signaling pathways are determined by a mutual influence on each other, resulting in a dynamic and complex crosstalk. It consists of various dynamic processes including a series of overlapping phases: hemostasis, inflammation response, new tissue formation, and tissue remodeling. Interruption or deregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 112 publications
(136 reference statements)
0
33
0
Order By: Relevance
“…To promote the WH, several EMFs with different frequencies, square waveform, and intensity have been explored [8,[23][24][25][26][27][28]. In fact, several studies have evaluated the effects of PEMF on chronic diabetic foot ulcers but using different PEMF parameters and with contradictory findings [29,30], suggesting that combinations of intensity and treatment period may produce different effects on extracellular matrix synthesis and remodeling, cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To promote the WH, several EMFs with different frequencies, square waveform, and intensity have been explored [8,[23][24][25][26][27][28]. In fact, several studies have evaluated the effects of PEMF on chronic diabetic foot ulcers but using different PEMF parameters and with contradictory findings [29,30], suggesting that combinations of intensity and treatment period may produce different effects on extracellular matrix synthesis and remodeling, cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that reduced or delayed WH may be a consequence of an altered equilibrium between free radicals and antioxidants allowing the wound to proceed unchecked. In fact, in the elderly subject, WH was delayed, and interestingly, the levels of wound antioxidants decrease with aging [23].…”
Section: Discussionmentioning
confidence: 99%
“…While Helmholtz coils produce fields with limited intensities (less than a few milli Teslas) and the other instruments based on magnets have a very limited range of frequencies, our new design can apply various exposure conditions with a broad range of low frequencies (0–70 Hz/0.001 Hz accuracy) and also the maximum intensity of 150 mT. This range of amplitude and frequency can generate interesting non-ionizing, non-thermal effects 29 which has recently attracted researchers’ attention for their new biomedical applications 10 , 30 , 31 . Moreover, as noted above, the ability of long-time exposures in an optimal culture condition is a prominent feature of our new design.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, many studies have reported the positive effects and therapeutic uses of ELF-EMF e.g. in wound repair 8 , 9 , bone repair, pain management 10 , and Alzheimer’s disease (AD) 11 . Recent in vitro and in vivo studies have shown that exposure to ELF-EMF directly influenced human cells where it induced various effects; for instance, altered reactive oxygen species (ROS) levels 12 , increased intracellular Ca 2+ 13 , 14 , changed expression of genes involved in cell cycle, metabolism, autophagy, apoptosis pathways 15 17 , and inhibited proliferation 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Impaired WH is a result of the failure of normal progression through the phases [ 26 ]. In the last few years, an increasing number of reports have evaluated the effects of pharmacologic or physical modulation of tissue repair [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%